PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 005 BAGAN BARAT KEC.BANGKO - ', Agustam; Alpusari, Mahmud; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstarak: The problem in this research is the lack of ability of science teaching in the fourth grade primary school 005 Chart of the West can be seen on the symptoms of the inability in learning the influence of the natural appearance and sky, low ability students in learning the effects of nature and the sky in the life of the community in accordance with the Their life. Lack of knowledge of students both morally and materially to the creativity peruhan nature. lack of skills in understanding concepts, reasoning, and problem solving, about science teaching fourth grade. Based on the problems it is necessary to find a way to solve the problem. Among them change the models of learning. Therefore in this study, researchers will implement cooperative learning model STAD learning. This study is classroom action research conducted by two cycles each cycle consisting of two meetings. The implementation of cooperative learning model STAD knowingly engage students to engage actively and creatively. Subjects in this study were students of class IV SDNegeri 005 West Bagan Semester II. This research data collection instruments consisted of the observation sheet activities of teachers and students and a test sheet to repeat the cycle end. This research is a classroom action research (PTK), the study aims to increase students' appreciation second semester Elementary School 005 West Bagan. The results of this study show that the implementation of cooperative learning model STAD can improve students' learning science appreciation Elementary School 005 West Bagan, with the average value becomes a value 90.8 42.9 early in the second cycle. The average value of teacher activity also increased from an average of 75.00 into 91.66. Activities of students also increased from an average of 70.83% in the first cycle to 91.66%. Thus the research hypothesis if applied local wisdom approach the learning ability of students IPA Class IV ElementarySchool 005 West Bagan increased, proven. Key Words: learning outcomes IPA inprove class IV